Readers Respond: Student-Athlete Development: Balance is Key - Hill, Thomas L. (My University, 1994)
The author responded to the previous article by Gerdy by arguing that having advisors/athlete development staff in athletics is not necessarily a detriment to athletes as a unique population on campus. He argued that athletic staff can liaise with student affairs staff and be hired with appropriate knowledge and experience.
Keywords: well-being